2015
DOI: 10.1063/1.4921182
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal stability and reliability of HfO2 based resistive random access memory devices with cross-bar structure

Abstract: Articles you may be interested inRole of the electrode metal, waveform geometry, temperature, and postdeposition treatment on SET and RESET of HfO2-based resistive random access memory 1R-cells: Experimental aspects J. Vac. Sci. Technol. B 33, 01A107 (2015); 10.1116/1.4905426The effect of thermal treatment induced inter-diffusion at the interfaces on the charge trapping performance of HfO2/Al2O3 nanolaminate-based memory devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Based on the phenomena described above, the resistive switching behaviors are agreement with conductive filament model very well. Generally speaking, there are metal CF 27,35-37 and oxygen vacancy CF [38][39][40] in the binary oxide dielectric such as HfO 2 film. Many studies have been reported that active electrodes such as Ag 4,41 and Cu [35][36][37] tends to migrate and form CF connecting with counter electrodes, playing an important role in resistive switching process.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the phenomena described above, the resistive switching behaviors are agreement with conductive filament model very well. Generally speaking, there are metal CF 27,35-37 and oxygen vacancy CF [38][39][40] in the binary oxide dielectric such as HfO 2 film. Many studies have been reported that active electrodes such as Ag 4,41 and Cu [35][36][37] tends to migrate and form CF connecting with counter electrodes, playing an important role in resistive switching process.…”
Section: Resultsmentioning
confidence: 99%
“…HfO 2-x also shows excellent performance in the applications of band width [32] and resistance range [30]. The retention of the HfO 2-x system at high temperature [33] and low temperature [34] has also been verified. Chand et al designed a structure of the Ti/Al 2 O 3 /TiO 2 /TiN device by inserting an Al 2 O 3 layer between the Ti top electrode and HfO 2-x layer and conducting high-temperature vacuum annealing and postmetal annealing treatments for achieving the thermal stability and reliability [33].…”
Section: Introductionmentioning
confidence: 74%
“…The retention of the HfO 2-x system at high temperature [33] and low temperature [34] has also been verified. Chand et al designed a structure of the Ti/Al 2 O 3 /TiO 2 /TiN device by inserting an Al 2 O 3 layer between the Ti top electrode and HfO 2-x layer and conducting high-temperature vacuum annealing and postmetal annealing treatments for achieving the thermal stability and reliability [33]. On the other hand, Fang et al adopted a Pt/HfO x /TiN structure to stabilize the performance of RRAM in low temperature [34].…”
Section: Introductionmentioning
confidence: 75%
“…Among them, metal-oxide-based resistive switching memories such as HfO 2 have proven to have the best resistive switching performances in terms of, e.g., endurance, retention, and variability. Excellent resistive switching has been reported when using metal bottom electrodes [18,19]. HfO 2 -based resistive switching memory with ITO electrode can also be used for flexible and transparent electronic devices [20].…”
Section: Introductionmentioning
confidence: 99%